2005
DOI: 10.1017/s0263574704000669
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting adaptable passive behaviour to influence natural dynamics applied to legged robots

Abstract: This paper reports on the use of a particular actuator in the field of legged robots. The proposed actuator, the Pleated Pneumatic Artificial Muscle, has some interesting characteristics which makes it suitable for machines which move by means of legs. An important issue is the actuator's adaptable passive behaviour which allows the stiffness of a joint that is actuated by two antagonistically coupled muscles, to be varied online. The natural frequency of the system can thus be changed in order to reduce contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…The optimisation of the passive system properties has also been discussed under more dynamic conditions. In this context, [22,23], demonstrated that tracking a small amplitude oscillatory motion of a pendulum can be made efficient by matching the (constant) stiffness of the actuators with the natural stiffness of the reference trajectory. With a similar objective in [20], the authors combined trajectory tracking with adaptation of the constant joint stiffness to its optimal value.…”
Section: Introductionmentioning
confidence: 99%
“…The optimisation of the passive system properties has also been discussed under more dynamic conditions. In this context, [22,23], demonstrated that tracking a small amplitude oscillatory motion of a pendulum can be made efficient by matching the (constant) stiffness of the actuators with the natural stiffness of the reference trajectory. With a similar objective in [20], the authors combined trajectory tracking with adaptation of the constant joint stiffness to its optimal value.…”
Section: Introductionmentioning
confidence: 99%
“…The mean value p m will determine the joint stiffness and will be controlled in order to influence the natural dynamics of the system [19]. Feeding back the joint angle b and using expression (2), Dp can be determined by:…”
Section: Robot Controlmentioning
confidence: 99%
“…Doing so includes the muscle actuator characteristics, which allows the limitations in the motion of the pendulum to be studied. Detailed information on the simulation model can be found in (Verrelst, 2005a) for a one degree of freedom setup and in (Verrelst, 2005b) for the complete biped, elaborated on in section 5. To test the robustness, model parameter uncertainties are introduced in the simulation model, e.g.…”
Section: Simulatormentioning
confidence: 99%